QUALITY OF LIFE OF PATIENTS WITH SEVERE KNEE OSTEOARTHRITIS IN HUNGARY: CROSS-SECTIONAL STUDY - Huda ALFATAFTA; Mahmoud ALFATAFTA; Faten AMER; Sahar HAMMOUD; Lu ZHANG; Bálint MOLICS; Imre BONCZ (Cluj University Press, 2022)
Introduction: Knee osteoarthritis (OA) is a chronic musculoskeletal disease that is associated with mortality, disability, and low quality of life. In Hungary, the number of patients diagnosed with severe knee osteoarthritis is dramatically increasing yearly. Objective: This study aims to assess the quality of life among patients with severe knee osteoarthritis who undergo knee replacement surgery after one month to assess their quality of life (QoL). Material and Method: Ten patients (6 female, 4 male, 70±4 years, 30.7±3.4 kg/m2) with severe knee osteoarthritis were included from an orthopedic clinic in Pécs, Hungary. The SF-36 questionnaire (Hungarian version) was used to assess QoL of the patients one month prior to knee replacement surgery. Results: The participants with severe knee OA reported allow overall average of pain (40.95%), role limitations due to physical health (42.5%), and role limitations due to emotional problems (46.7%) that reduced their QoL. In addition, there are significant differences between women and men in some domains. Women had significantly lower physical functioning and role limitations due to emotional problems than men, by 42.8% (p=0.03) and 73.3% (P=0.005), respectively. Moreover, women had a higher feeling of pain than men; however, the differences was insignificant. Conclusions: Patients with severe knee osteoarthritis have low quality of life and severe pain during daily activities. Furthermore, women with severe knee OA had significantly higher pain and lower quality of life than men due to their emotional status. Further studies with large sample sizes are needed. Received 2022 June 30; Revised 2022 July 15; Accepted 2022 July 21; Available online 2022 June 30; Available print 2022 August 30.